Acúmulo de sais no solo, produtividade e teores de íons no milho irrigado com águas salinas de forma contínua ou alternada - Barbosa, Felipe de Sousa (2010)
Irrigation with water containing excess salts may, depending on the content and of these types, alter negatively the development of crops. One effect of salinity is osmotic in nature, directly affecting crop yields. Another effect of irrigation with saline water on the corn crop is the elevation of sodium and chlorine in the chloroplasts of plants, which can result in decreased photosynthetic rate. The use of correct techniques of management aims to enable the use of water with high salt content. The aim of this study is to evaluate the use of water of high salinity in irrigation, in a continuous or alternating with water of low salinity on the accumulation of salts in the soil and the vegetative growth, productivity, and accumulation of ions in plants corn. The study was conducted in an experimental field of the UFC. The experimental design was a randomized complete block. Irrigated with three water sources with electrical conductivities of 0.8, 2.5 and 5.0 dS m-1, combined into seven treatments. The strategy of the cyclic use of low water and high salinity reduces the accumulation of salts in the soil, notably in the plant root zone, resulting in less accumulation of potentially toxic ions (Na and Cl) in shoots of corn plants. The use of water of high salinity (EC 5.0 dS m -1) during the entire cycle of corn genotype analyzed, significantly reduced the productivity in the 2008-2009 test. Irrigation water with EC up to 5.0 dS m-1 doesn’t affect plant height and stem diameter. The salinity in the way it was imposed, doesn’t reduce plant growth. The cyclic use of saline water allows the partial substitution of low salinity water for irrigation, which also reduces the impacts on soil and on culture.